The eyes of Texas - Sinclair, John Lang, 1879-1947.
Poem entitled "The Eyes of Texas."
Positive and negative photocopies.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Texas -- Poetry